The North American trade region: The reasons for its creation and its initial economic repercussions - Harald Victor Proff (Intereconomics, 1993)
The North American Free Trade Agreement (NAFTA) that is to take effect at the beginning of 1994 will create a free trade area between three economies which differ substantially in terms of size and stage of development. What were the reasons that led the unequal partners, the USA, Canada and Mexico, to enter into closer trade integration? What will be the economic consequences for the countries involved and for world trade?
Keywords: 330; NAFTA